2016
DOI: 10.1159/000455856
|View full text |Cite
|
Sign up to set email alerts
|

An Outbreak of Acute Hepatitis Caused by Genotype IB Hepatitis A Viruses Contaminating the Water Supply in Thailand

Abstract: Background: In 2000, an outbreak of acute hepatitis A was reported in a province adjacent to Bangkok, Thailand. Aims: To investigate the cause of the 2000 hepatitis A outbreaks in Thailand using molecular epidemiological analysis. Methods: Serum and stool specimens were collected from patients who were clinically diagnosed with acute viral hepatitis. Water samples from drinking water and deep-drilled wells were also collected. These specimens were subjected to polymerase chain reaction (PCR) amplification and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…It is resistant to salt and low pH (Hollinger and Emerson, 2007) and can persist in the environment, particularly in the water. Occasional waterborne outbreaks are described, like recently in Korea (Shin et al, 2017), and contamination of water is proven especially in situations of low sanitation level (Ruchusatsawat et al, 2016). Thus, it is not surprising that untreated water was associated in this meta-analysis with sporadic HAV infection.…”
Section: Fig 2 Forest Plot Of the Association Of Hepatitis A Infection With Low/untreated Water Consumption For Mixed Populationsupporting
confidence: 50%
“…It is resistant to salt and low pH (Hollinger and Emerson, 2007) and can persist in the environment, particularly in the water. Occasional waterborne outbreaks are described, like recently in Korea (Shin et al, 2017), and contamination of water is proven especially in situations of low sanitation level (Ruchusatsawat et al, 2016). Thus, it is not surprising that untreated water was associated in this meta-analysis with sporadic HAV infection.…”
Section: Fig 2 Forest Plot Of the Association Of Hepatitis A Infection With Low/untreated Water Consumption For Mixed Populationsupporting
confidence: 50%
“…However, despite these disinfection steps, outbreaks occur − and some authors reported the detection of virus particles in drinking water, demonstrating that viruses can sometimes go through the disinfection processes. , This could result from inadequate treatment (technical failure, high viral concentration, or viral resistance) and suggests that virus inactivation might be overestimated in laboratory conditions. An explanation could be that the efficiency of treatments is usually evaluated using purified viruses, cell culture-adapted strains, and sometimes virus surrogates such as bacteriophages.…”
Section: Introductionmentioning
confidence: 99%
“…This deployable system has offered the application of real-time metagenomic sequencing in POC testing for virus outbreaks, including chikungunya, Ebola, and hepatitis C viruses in human blood samples [22]. Whole-genome sequencing of zoonotic pathogens in real time has contributed to the identification and characterization of an emerging virus outbreak using epidemiology with genotypic diversity, geographical origin, and infectious source [23][24][25][26][27]. Herein, multiplex PCR-based nanopore sequencing facilitated the nearly complete genome sequencing of HAV directly from human samples containing low copy numbers of viral RNA within 8 h using the singleplex assay.…”
Section: Discussionmentioning
confidence: 99%